Eisegénesis de la celebración del matrimonio en la comunidad “Guanto Grande” de Saquisilí - Mera Nacevilla, Nancy Alexandra (2018)
The research gathers data about the marriage of the Guanto Grande community, its rites and traditions have a significant process in the indigenous culture of Cotopaxi, especially in Saquisilí, where the largest population is indigenous. It is observed how social phenomena, environmental and media influences the process of marriage. The valuation of their customs and the meaning that this has about their culture. The project mentions priests who passed through the parish and give their testimony that over the years changes the way people celebrate and think. The changes that have marked a difference in the celebration of marriage as the duration of the celebration are evident, it is clear acculturation and whitening in the celebration of the indigenous marriage to abandon their ancestral customs to imitate the mestizo, this by the departure of many indigenous to the urban sector. As a result of the migratory phenomenon, it aims to highlight the meaning of clothing, rites, food and other details, which are carried out before and after marriage, as well as the party that involves the whole community and allows discovering their worldview. The importance of the community in the care and preservation of ancestral customs can be noted. They glimpse the possible consequences of the loss of customs.